MUSICAL ICONOGRAPHY IN THE WORKS OF Z. KURCHYNSKY (GENRES, STYLES, CHRONOTOPE) - Velykanych, Sofiia (International Journal of Innovative Technologies in Social Science, 2020)
The article highlights the figure of a prominent Lviv sculptor and graphic artist of Polish origin, who clearly showed his creative personality in the decor of architectural structures of Lviv and other forms of sculptural specimens in the late XIX - early XX centuries. The found samples of the artist’s appeal to musical symbolism and figures of musical culture in monumental and portrait sculpture are analyzed. The genre classification of the found artifacts in the declared subject is carried out, and also samples from group of a sculptural ornament as key in research are analyzed in detail. The search for sources of such interest in the creative biography of the artist and the establishment of causal links in the context of artistic processes of the time. Emphasis is placed on the role of personalities who met on the artistic path of the sculptor, as well as on specific examples of their influence on the creative realization of Z. Kurchynsky.